The bundling sales pricing strategy of the closed-loop supply chain under patent protection - Xiaogang Cao; Cuiwei Zhang; Jie Liu; Hui Wen; Bowei Cao (Modern Supply Chain Research and Applications, 2024)
Purpose -The purpose of this article is based on the unit patent license fee model in the closed-loop supply chain. Design/methodology/approach - This paper analyzes the impact of the bundling strategy of the retailer selling new products and remanufactured products on the closed-loop supply chain under the condition that the original manufacturer produces new products and the remanufacturer produces remanufacturing products. Findings - The results show that alternative products can be bundled, and in many cases, the bundling of remanufactured products and new products is better than selling alone. Originality/value - If the retailer chooses bundling, for the remanufacturer, when certain conditions are met, the benefits of bundling are greater than the separate sales at that time; for the original manufacturer, when the recycling price sensitivity coefficient is high, the bundling is better than separate sales.
Keywords: 650; Closed-loop supply chain; Bundling sales; Alternative product; Patent licensing; Stackelberg game